Joint kinetics differences during the take-off of forward and backward rotating dives - Mathiyakom, W.; McNitt-Gray, J. L.; Munkaasy, B. A.; Eagle, J.; Gabriele, J. (1998)
In conclusion, the significant differences in joint kinetics observed during the take-off of forward and backward rotating dives suggest dry land training activities need to be designed specifically for each dive. Training activities for forward rotating dives need to emphasize relatively quick (0.25s) reaction force production using primarily ankle extensors, knee extensors, and hip flexors. In contrast, training activities for backward rotating dives need to emphasize generation of reaction forces over a relatively long period of time (e.g. 0.45s) using primarily ankle extensors, knee flexors and extensors, and hip extensors.